Pengaruh Literasi Keuangan Terhadap Perilaku Pengelolaan Keuangan Melalui Kontrol Diri Sebagai Variabel Intervening pada Siswi Asrama MAN 2 Jember - Malikatul Wakhidah (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
One of the essential life skills in the 21st century is financial competence, which reflects an individual’s ability to manage finances wisely. Several factors, including financial literacy and self-control, influence financial management behavior. The ability to manage finances poses a particular challenge for female students at MAN 2 Jember who live in dormitories, as they must manage limited monthly allowances to avoid overspending. Although dormitory students at MAN 2 Jember have received economics education at school as a foundation for financial knowledge, the phenomenon of running out of money before the end of the month remains common due to the lack of financial record-keeping and the habit of online shopping. This study aims to examine the effect of financial literacy on financial management behavior, both directly and indirectly through self-control. This research employed a causal quantitative approach. The research location was determined purposively at MAN 2 Jember. The population consisted of 160 female dormitory students, with a sample of 114 students selected using a simple random sampling technique. Data were collected through questionnaires, interviews, and documentation. Data analysis was conducted using the Structural Equation Model–Partial Least Squares (SEM-PLS) approach, assisted by SmartPLS version 4.0. The results indicate that financial literacy has a positive and significant effect on financial management behavior. Financial literacy also has a positive and significant effect on self-control, while self-control positively and significantly affects financial management behavior. In addition, financial literacy has a significant indirect effect on financial management behavior through self-control. Therefore, it can be concluded that good financial literacy contributes to the development of prudent financial management behavior mediated by strong self-control, among the dormitory students of MAN 2 Jember.
The Influence of Financial Literacy on Financial Management Behavior Through Self-Control as an Intervening Variable Among Female Dormitory Students of MAN 2 Jember
Reva_21 Mei 2026
Keywords: Financial Literacy; Self-Control; Financial Management Behavior; Dormitory Students